UTILIZATION OF TUBA ROOT EXTRACT (Derris elliptica Benth.) AS A VEGETABLE PESTICIDE FOR CONTROL OF THE PEST Spodoptera frugiperda J.E Smith - Flora Pasaru; Burhanuddin Haji Nasir; Mutmainah; Sri Anjar Lasmini; Nova A. Panggalo; Ivonela Karolina Yahya (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2026)
Fall armyworm (Spodoptera frugiperda) is one of the main pests of corn. The intensity of S. frugiperda attacks was quite high, namely 57.62%. Controlling S. frugiperda using tuba root extract is an environmentally friendly pest control technique. The research aims to determine the concentration of tuba root extract (Derris elliptica Benth) that is effective in controlling S. frugiperda. Preliminary test research was carried out at the Plant Pest and Disease Laboratory, Faculty of Agriculture, Tadulako University, and further tests were carried out in Oloboju Village, Sigi Biromaru District, Sigi Regency, from July 2023 to October 2023. Preliminary tests used a Completely Randomized Design (CRD) and for further tests in the field used a Randomized Block Design (RBD) consisting of 5 treatments, namely without extract (K0), concentration 2, 5% tuba root extract (K1), 5% (K2), 10% (K3), and 20% (K4). The results of research in the laboratory showed that the K4 was able to kill S. frugiperda larvae and inhibit the development of the larvae into pupae. Based on LC50 probit analysis, tuba root extract can kill S. frugiperda larvae above 50%. Field application shows that a concentration of 20% (K4) is able to suppress attacks by S. frugiperda larvae, and can increase corn production. Application of 20% concentration of tuba root extract can kill S. frugiperda larvae by 53.33%, inhibit the development of larvae into pupae by 46.67%, suppress attacks by 22.78%, and increase production corn amounted to 3.48 tonnes/ha.